INFORMATION SYSTEM DESIGN USING CUTOMER RELATIONSHIP MANAGEMENT (CRM) METHOD AT PAGLAK PETUNG CAFE AND ART IN BANYUWANGI DISTRICT - Nur Indahsari, Luluk; Yunita, Irma; Fatah, Zaehol (Jurnal Teknik Informatika (Jutif), 2024)
The development of information and communication technology (ICT) has transformed the business world. The success of a cafe is now measured not only by its profits but also by its ability to build long-term customer relationships. Customer Relationship Management (CRM) is a strategy for building and maintaining good relationships with customers. Paglak Petung Cafe and Art in Banyuwangi faces customer management challenges as the number of customers increases. This research aims to design and build a CRM-based information system for the cafe to enhance the efficiency of managing customer data, orders, and promotions. The findings show that the developed system can improve the customer experience and provide a competitive advantage for the cafe. The system also facilitates management in making more accurate data-driven decisions